ANALISIS KELENGKAPAN BERKAS REKAM MEDIS DI PUSKESMAS KUTA UTARA - Widiarta, Marselinus Gede; Hardy, I Putu Dedy Kastama; Yunita Sari, Ni Kadek (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022, 2022)
ABSTRACT Every health facility, from primary/primary, secondary, tertiary levels is required to maintain medical records. Medical records are an important part of health services. The quality of medical records also determines the quality of health services. The North Kuta Health Center is one of the health centers in Badung Regency whose medical records have not yet reached 100%. The purpose of this study was to describe the completeness of patient identification and authentication of medical record files at the North Kuta Health Center and identify factors that affect the completeness of patient identification and authentication of medical record files. The research method used is a quantitative and qualitative method with a sequential explanatory design. The research sample based on the slovin formula was 92 medical record files. There were seven informants consisting of doctors, nurses, midwives, registration officers and medical records officers. The results showed that the average completeness of filling in patient identification and authentication of medical record files was quite complete but still less than the standard of completeness set by the Indonesian Ministry of Health of 100%. The lack of special training on filling out medical records, the occurrence of human errors due to lack of awareness and discipline of officers in filling out medical record files, patients not carrying identities, lack of socialization of SOPs for filling medical records, and the absence of sanctions for officers who do not fill out medical record files completely are factors that affect the completeness of patient identification and authentication of medical record files. So it is advisable to socialize the SOP for filling out medical records intensively, giving warnings or sanctions to officers who do not fill out medical record files completely and giving awards to officers who fill out medical records completely. Keywords : Completeness, factors, Medical Records, Health Services